2020
DOI: 10.12998/wjcc.v8.i19.4331
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of a nomogram to predict the risk of ovarian metastasis in gastric cancer: Based on a large cohort

Abstract: BACKGROUND Ovarian metastasis is a special type of distant metastasis unique to female patients with gastric cancer. The pathogenesis of ovarian metastasis is incompletely understood, and the treatment options are controversial. Few studies have predicted the risk of ovarian metastasis. It is not clear which type of gastric cancer is more likely to metastasize to the ovary. A prediction model based on risk factors is needed to improve the rate of detection and diagnosis. AIM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Due to the detected ultrasound pathology, she was thoroughly screened for tumour markers, which were found to be normal. A 12-year study in a cohort of 1,696 women showed elevated CA-125 levels in patients with Krukenberg tumours, which decreased after its eradication (5) . Similarly, Aziz et al reported an increase in CA-125 and CA-19-9 in Krukenberg tumours (21) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the detected ultrasound pathology, she was thoroughly screened for tumour markers, which were found to be normal. A 12-year study in a cohort of 1,696 women showed elevated CA-125 levels in patients with Krukenberg tumours, which decreased after its eradication (5) . Similarly, Aziz et al reported an increase in CA-125 and CA-19-9 in Krukenberg tumours (21) .…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic ovarian tumours often pose a diagnostic challenge. In order to distinguish Krukenberg tumours from primary ovarian carcinomas, many diagnostic models have been developed that take into account clinical, biochemical and radiological features to accurately define these two types of cancer (5,19,20) . It is estimated that the primary source of Krukenberg tumour is unknown in approximately 15% of women (1) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gao et alreported premenopausal status, tumor invasion depth, number of positive lymph nodes, and no ERβ expression as factors independently predicting metachronous ovarian metastasis [ 17 ]. Li et alconstructed a nomogram including age, N stage, Lauren type, signet-ring cell component, estrogen receptor expression, neutrophil/lymphocyte ratio, and serum CA125 for predicting ovarian metastasis in GC, with an area under the curve (AUC) for the model of 0.819 [ 18 ]. However, both synchronous and metachronous ovarian metastases were involved in this study, which may not mimic the real-world setting.…”
Section: Introductionmentioning
confidence: 99%